2016
DOI: 10.1080/21623945.2016.1195044
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human adipogenesis by miR125b-5p

Abstract: MicroRNAs (miRNAs) are non-coding RNAs that regulate target gene expression at the post-transcriptional level and are supposed to be implicated in the control of adipogenesis. We aimed to identify miRNAs which are involved in the regulation of human adipogenesis and searched for their molecular targets.Applying microarray-analysis we identified miR125b-5p as upregulated during human adipocyte differentiation, although its role during adipogenesis is unknown. We identified and characterized the matrix metallopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
(43 reference statements)
4
15
0
1
Order By: Relevance
“…Our findings are partly in line with previous research investigating the role of miR-125b-5p on adipogenesis where it is observed that miR-125b-5p downregulates the anti-adipogenic gene MMP11 in human, indicating that miR-125b-5p via MMP11 positively regulate adipogenesis (Rockstroh et al, 2016). Conversely, the same study demonstrated a direct effect of reduction in fat accumulation through overexpression of miR-125b-5p (Rockstroh et al, 2016). In addition to the role of miR-125b-5p on lipid metabolism in human, its regulatory role has been investigated in other organisms including zebrafish and mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are partly in line with previous research investigating the role of miR-125b-5p on adipogenesis where it is observed that miR-125b-5p downregulates the anti-adipogenic gene MMP11 in human, indicating that miR-125b-5p via MMP11 positively regulate adipogenesis (Rockstroh et al, 2016). Conversely, the same study demonstrated a direct effect of reduction in fat accumulation through overexpression of miR-125b-5p (Rockstroh et al, 2016). In addition to the role of miR-125b-5p on lipid metabolism in human, its regulatory role has been investigated in other organisms including zebrafish and mice.…”
Section: Discussionsupporting
confidence: 92%
“…Our DNA methylation analysis results showed the association between cg03891346 and waist circumference in the RS. Our findings are partly in line with previous research investigating the role of miR-125b-5p on adipogenesis where it is observed that miR-125b-5p downregulates the anti-adipogenic gene MMP11 in human, indicating that miR-125b-5p via MMP11 positively regulate adipogenesis (Rockstroh et al, 2016). Conversely, the same study demonstrated a direct effect of reduction in fat accumulation through overexpression of miR-125b-5p (Rockstroh et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Several miRNA species, like miR-130 or miR-27b, regulate adipogenic differentiation by targeting the expression of peroxisome proliferator-activated receptor gamma (PPARγ), the master regulator of adipogenesis [47]. Along the same line, miR-125b-5p, which is upregulated during human adipogenesis, downregulates the antiadipogenic matrix metalloproteinase 11 and directly inhibits adipogenesis itself [79]. Zhang et al [76] demonstrated that overexpression of miR-378 apparently prevents and treats obesity by activating the muscle pyruvate-phosphoenolpyruvate futile cycle and enhancing lipolysis in adipose tissue.…”
Section: The Role Of Epigenetics and Developmental Programming In Thementioning
confidence: 99%
“…These miRNAs were downregulated in adipose tissue. There are also miRNAs that inhibit adipogenesis but upregulate adipocyte differentiation, such as miR-125 [42] and miR-34a, which target CD36, LXRα, PGC1α, or FASN [42,43]. In addition to adipomiRs, circulating miRNAs such as miR-142, miR-140, miR-138, miR-15a, b and miR-376a are also suggested to be predictive markers for adipose dysfunction [44,45].…”
Section: Discussionmentioning
confidence: 99%